The Effects of Gingerol on Lipid and Protein Profiles in Alloxan-Induced Diabetic Rats - Murad, Intisar Mohammad; A.N.AlZamely, Dr. Hayder (American Journal of Biology and Natural Sciences, 2025)
This study investigated the impact of gingerol, the main bioactive phenolic compound in Zingiber officinale, on lipid and protein profiles in alloxan-induced diabetic rats. Diabetes mellitus is associated with profound metabolic disturbances, including dyslipidemia and alterations in serum protein levels, which contribute to the progression of cardiovascular complications.30 Male Wistar rats were divided into therr groups (n = 10 per group) : non-diabetic control, diabetic control, diabetic rats treated with gingerol (2 mg/kg body weight) .Diabetes was induced by a single intraperitoneal injection of alloxan (150 mg/kg). Treatments were administered orally for four weeks. Serum lipid parameters (total cholesterol, triglycerides, HDL-C, LDL-C, VLDL-C) and total protein profile levels(total protein , albumin , globulin , fibrinogen) were analyzed using standard biochemical methods. Histopathological examination of the pancreas was also performed to assess tissue alterations. Results revealed that gingerol supplementation significantly reduced total cholesterol, triglycerides, LDL-C, and VLDL-C while increasing HDL-C compared to the diabetic control group (p < 0.05). Serum total protein levels were significantly improved, approaching near-normal values. Histopathological findings demonstrated amelioration of hepatic architecture in gingerol-treated rats compared to severe fatty changes observed in untreated diabetic animals. The effects of gingerol were comparable to alloxan, suggesting its potential as a natural therapeutic agent for improving lipid and protein profiles in diabetes. These findings support the inclusion of gingerol-rich preparations as a complementary approach in diabetes management.